2013
DOI: 10.1128/aem.03029-12
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental Dispersal of Bacteria and Archaea by Transpacific Winds

Abstract: f Microorganisms are abundant in the upper atmosphere, particularly downwind of arid regions, where winds can mobilize large amounts of topsoil and dust. However, the challenge of collecting samples from the upper atmosphere and reliance upon culture-based characterization methods have prevented a comprehensive understanding of globally dispersed airborne microbes. In spring 2011 at the Mt. Bachelor Observatory in North America (2.8 km above sea level), we captured enough microbial biomass in two transpacific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(204 citation statements)
references
References 26 publications
6
197
0
1
Order By: Relevance
“…Chao 1 analysis of the pyrosequencing data showed that the number of bacterial species in the air samples ranged from 270 to 410. In a previous study, microarray analysis detected approximately 400 species in airborne bacterial communities on mountains (Smith et al, 2013), consistent with the estimated numbers observed in this study. In sequential surveys of a mountain site, airborne microbial communities at the higher altitudes of mountains also included highly diverse bacterial populations (Bowers et al, 2012).…”
Section: Bacterial Community Structures Among Three Altitudessupporting
confidence: 75%
See 1 more Smart Citation
“…Chao 1 analysis of the pyrosequencing data showed that the number of bacterial species in the air samples ranged from 270 to 410. In a previous study, microarray analysis detected approximately 400 species in airborne bacterial communities on mountains (Smith et al, 2013), consistent with the estimated numbers observed in this study. In sequential surveys of a mountain site, airborne microbial communities at the higher altitudes of mountains also included highly diverse bacterial populations (Bowers et al, 2012).…”
Section: Bacterial Community Structures Among Three Altitudessupporting
confidence: 75%
“…In addition, airborne microorganisms on North American mountains (2,700 m above sea level) were found to change in response to Asian dust events that included highly diverse bacterial species (Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The westerly winds blowing over East Asia would transport airborne bacteria to the high-altitude atmosphere over the Noto Peninsula and North American mountains (Smith et al, 2013). Our box plots analysis suggested that changes in the bacterial diversity in the dust samples would be more stable than in the non-dust samples (Fig.…”
Section: Comparing the Community Structures Of Atmospheric Bacteria Bmentioning
confidence: 90%
“…Back trajectories on 19 March 2013 and 20 March 2015 came from the Asian desert region to the Noto Peninsula. Some Bacillus species were predominantly detected at high altitudes above the Taklamakan Desert (Maki et al, 2008) and above downwind areas during Asian dust events (Maki et al, 2010(Maki et al, , 2013Smith et al, 2013;Jeon et al, 2011;Tanaka et al, 2011) (Table 2). Bacillus species are the most prevalent isolates obtained from mineral dust particles collected over downwind areas (Hua et al, 2007;Gorbushina et al, 2007).…”
Section: Dominant Bacterial Populations In the Air Masses Transportedmentioning
confidence: 99%
See 1 more Smart Citation